Canada’s Earthquakes: ‘The Good, the Bad, and the Ugly’ - Cassidy, J. F.; Rogers, G. C.; Lamontagne, M.; Halchuk, S.; Adams, J. (Geoscience Canada, 2010)
Much of Canada is ‘earthquake country’. Tiny earthquakes (that can only be recorded by seismographs) happen every day. On average, earthquakes large enough to be felt occur every week in Canada, damaging earthquakes are years to decades apart, and some of the world’s largest earthquakes are typically separated by intervals of centuries. In this article, we provide details on the most significant earthquakes that have been recorded in, or near, Canada, including where and when they occurred, how they were felt, and the effects of those earthquakes. We also provide a brief review of how earthquakes are monitored across Canada and some recent earthquake hazard research. It is the results of this monitoring and research, which provide knowledge on earthquake hazard, that are incorporated into the National Building Code of Canada. This, in turn, will contribute to reduced property losses from future earthquakes across Canada. SOMMAIRE Un bonne partie du Canada est un ‘pays de séismes’. De petits séismes (que seuls les séismographes peuvent enregistrer) s’y produisent quotidiennement. En moyenne, un séisme assez fort pour qu’on le ressente s’y produit à intervalle d’une semaine; assez fort pour causer des dommages s’y produit à intervalle de quelques années à quelques décennies; alors que l’intervalle de récurrence des plus grands séismes est de l’ordre des siècles. Dans le présent article on trouvera des détails sur les plus importants séismes s’étant produits sur ou à proximité du territoire canadien, incluant le lieu et le moment, leurs manifestations et leurs répercussions. On y décrit sommairement les moyens de détection déployés sur le territoire canadien ainsi que quelques-unes des recherches récentes sur les risques sismiques. Ce sont les résultats des efforts de surveillance et des recherches sur les tremblements de terre qui ont été intégrés dans le Code national du bâtiment du Canada. Et cela aidera à amoindrir les répercussions des séismes à venir sur la propriété.